Suicidal feelings interfere with help-seeking in bullied adolescents [corrected]. - Yuko Kitagawa; Shinji Shimodera; Fumiharu Togo; Yuji Okazaki; Atsushi Nishida; Tsukasa Sasaki (PLoS ONE, 2014)
PURPOSE: Being bullied is associated with the manifestation of suicidal feelings, which sharply increase in middle(-late) adolescence. Whether or not bullied middle(-late) adolescents with suicidal feelings seek help is therefore a critical issue, given that help-seeking plays a key role in the prevention of suicide. The aim of the present study is to investigate the effects of bullying, suicidal feelings and the interaction between these two factors on help-seeking behavior in adolescents. METHODS: Japanese middle(-late) adolescents (aged 15-18 years; n = 9484) were studied using self-report questionnaires. The rate of adolescents who actually sought help was examined for bullying status and suicidal feelings. RESULTS: The rate of adolescents who sought help was significantly higher when they were bullied (p<0.001) and also when they had mild suicidal feelings (p<0.001), but not when they displayed serious suicidal feelings. In the case of adolescents who were bullied, however, having suicidal feelings significantly decreased the rate of help-seeking (OR = 0.47, p<0.05 and OR = 0.32, p = 0.002 for having mild and serious suicidal feelings, respectively). The decrease was remarkable when suicidal feelings were serious. Specifically, the decrease was significant in seeking help from peers and family members, who are the most frequent source of the help for adolescents, when they had serious suicidal feelings (OR = 0.21, p<0.01 and OR = 0.13, p<0.001, respectively). CONCLUSIONS: Suicidal feelings may interfere with help-seeking behavior, which could be critical in suicide prevention in bullied middle(-late) adolescents.